FORMATION OF EDUCATIONAL AUTONOMY OF STUDENTS OF ECONOMIC SPECIALITIES BY MEANS OF DIGITAL TECHNOLOGIES - Voshkolup, Hanna (Visnyk universytetu imeni Alʹfreda Nobeli͡a︡. Serii͡a︡: Pedahohika i psikholohii͡a, 2024)
The article is devoted to the problem of studying the peculiarities of the formation of educational autonomy of students of economic specialties by means of digital technologies. The purpose of the article is to identify the psychological and pedagogical features of the formation of educational autonomy of students of economic specialties by means of digital technologies. The tasks of the article are as follows: to characterize the theoretical foundations of the essence of educational autonomy as a pedagogical category; to determine the peculiarities of the formation of students’ learning autonomy skills; to prove the importance of the formation of educational autonomy among students of economic specialties; to determine the possibilities of digital technologies in the formation of educational autonomy among students of economic specialties. To achieve the goal, the following methods were used: literary analysis, generalization, comparison, systematization, etc. The article contains the following research results. A critical analysis of approaches to defining the essence of the concept of “learner autonomy” by various researchers was carried out. It was established that the concept of “pupil / student autonomy” was introduced in the early 1980s by Henri Holec, who defined this category as “the student’s ability to take responsibility for their own learning.” A theoretical study of the views of various researchers proved that the formation of students’ educational autonomy is mainly related to the process of mutual influence of motivation for educational activities and the success of completing educational tasks: motivation for learning is always characterized by the extent to which a student knows how to learn independently, demonstrating interest in learning, and, in turn, successful learning is impossible without motivation supported by the competence of self-regulated learning. In other words, learning autonomy is the student’s ability to be self-motivated and responsible for their own learning. It was found that one of the key aspects that should be taken into account when determining the independence of learning is whether we consider it as a means of achieving a goal (studying a certain educational module, subject, science) or as an end in itself (forming people as independent learners). These two options are not mutually exclusive, as they can both be part of our views on learning as a whole. Four main advantages of forming students’ learning autonomy have been identified: motivation (students strive to achieve their educational goals, but for this to happen, teachers must first help students set realistic learning goals); flexibility (an autonomous approach to learning is more flexible for both students and teachers, who can take on more of a coaching role, while students take the driver’s seat); lasting impact (learning to learn is an underrated skill, when students are in charge of their own learning, they learn what techniques and strategies work best for them); increasing involvement (using the autonomy of students, the teacher relies on their ability to solve problems, study the educational material and form their own opinion). The skills that students should develop in the process of autonomous learning are substantiated: setting goals; assessment of progress; time management; and self-motivation. Conclusions. The importance of the formation of academic autonomy of students of economics specialities has been proven, as independent thinking presents concepts, models and theories that students will use to solve real-world problems, honing their cognitive skills. The following advantages of using digital technologies in the direction of the formation of educational autonomy of students of economic specialties are outlined: making knowledge accessible; making knowledge understandable; providing flexibility and variability of training; and ensuring students’ interaction with the digital environment.